1998
DOI: 10.1046/j.1365-2575.1998.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

The Brave New World of development in the internetwork computing architecture (InterNCA): or how distributed computing platforms will change systems development

Abstract: This essay is a speculation of the impact of the next generation technological platform — the internetwork computing architecture (InterNCA) — on systems development. The impact will be deep and pervasive and more substantial than when computing migrated from closed computer rooms to ubiquitous personal computers and flexible client‐server solutions. Initially, by drawing upon the notion of a technological frame, the InterNCA, and how it differs from earlier technological frames, is examined. Thereafter, a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 1 publication
4
44
0
Order By: Relevance
“…Here is an example where the technology blurs roles, because a normal office worker with minimal training was able to develop the kind of functionality one may expect from a "systems developer" (Lyytinen, Rose and Welke 1998). Furthermore, as predicted by Lyytinen, Rose and Welke, in the Telkom and CSIR cases, the intranet technology was seen as creating a need for content providers with artistic or design skills.…”
Section: Content Providersmentioning
confidence: 96%
See 1 more Smart Citation
“…Here is an example where the technology blurs roles, because a normal office worker with minimal training was able to develop the kind of functionality one may expect from a "systems developer" (Lyytinen, Rose and Welke 1998). Furthermore, as predicted by Lyytinen, Rose and Welke, in the Telkom and CSIR cases, the intranet technology was seen as creating a need for content providers with artistic or design skills.…”
Section: Content Providersmentioning
confidence: 96%
“…Some intranet studies have found that the technology was in fact initiated by decentralized actors outside the IT group (Bhattacherjee 1998;Jarvenpaa and Ives 1996). Lyytinen, Rose and Welke (1998) stress the profound impact of the continuing evolution of Internet (and intranet) computing infrastructure on organizational processes. They predict that the ubiquitous nature of these technologies will blur traditional IS roles (e.g., users will become developers); demand new roles as technologies and media coalesce; and further that these changes will be on a much grander scale than ever before (e.g., as in the case of end user computing).…”
Section: Introductionmentioning
confidence: 99%
“…This argument is developed in (Lyytinen et al 1998). Systems operating in global, unbounded networks (like the Internet) might be inherently different is compared with typical systems that were available when ''classical'' ISD practices were originated.…”
Section: Do Classical Isd Practices Need Revision?mentioning
confidence: 96%
“…Thus, any application can be part of the intranet as long as the browser is primary client interface". Intranets are also sometimes referred to as 'glueware' or 'middleware' since they are utilized to interconnect heterogeneous systems through the browser and associated protocols and applications (Lyntinen et al, 1998).…”
Section: Intranet Backgroundmentioning
confidence: 99%